1994
DOI: 10.1128/aem.60.11.4189-4191.1994
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Nucleic Acid Probes for Detection of Poliovirus in Water Disinfected by Chlorine, Chlorine Dioxide, Ozone, and UV Radiation

Abstract: MilliQ water was inoculated with poliovirus type 1 strain LSc-1 and was treated with disinfectants, including chlorine, chlorine dioxide, ozone, and UV light. No relationship between probes and plaque assays were seen, demonstrating that viral nucleic acids were not destroyed. These findings suggest that nucleic acid probes cannot distinguish between infectious and noninfectious viruses and cannot be used in the evaluation of treated waters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…As mentioned above, HOCl can inactivate microbes ingested by leukocytes. At very low concentrations ClO 2 can also inactivate microbes in many in vitro experiments ( ). However, it is unclear whether in biological systems of higher organisms, such as human, ClO 2 will ever be produced in sufficient amounts to cause inactivation of invading microbes just like HOCl produced intracellularly in leukocytes does ( ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, HOCl can inactivate microbes ingested by leukocytes. At very low concentrations ClO 2 can also inactivate microbes in many in vitro experiments ( ). However, it is unclear whether in biological systems of higher organisms, such as human, ClO 2 will ever be produced in sufficient amounts to cause inactivation of invading microbes just like HOCl produced intracellularly in leukocytes does ( ).…”
Section: Discussionmentioning
confidence: 99%
“…Chlorite is dismutated to chloride and oxygen by chlorite dismutase (29). ClO 2 is known to have potent antimicrobial activity against bacteria, viruses, and protozoae (30)(31)(32)(33)(34)(35)(36)(37)(38). Despite a wealth of experimental data on the antimicrobial activity of ClO 2 , however, little is known about its biochemical mechanism.…”
mentioning
confidence: 99%
“…Chlorine dioxide (ClO 2 ) has been used as a disinfectant for both water and wastewater, in part because disinfection byproduct generation is minimal (Rittman, 1999). Recent research efforts have revealed that its efficacy against virus increases as the pH increases (Moore and Margolin, 1994). Narkis et al (1995) carried out research to analyze the effects of suspended solids on the performance of this disinfectant.…”
Section: Disinfection Methodsmentioning
confidence: 99%
“…The optimum UV wavelength range varies from 250 to 265 nm, with the ideal UV wavelength being around 260 nm. Liberti and Notarnicola (1999) performed a pilot study on pretreated wastewater including secondary, clarified, and clarified‐filtered wastewater. Results indicated a log inactivation value greater than 5 was achieved using a UV dose of 160 mW‐s/cm 2 for clarified effluent and a UV dose of 100 mW‐s/cm 2 in the case of clarified‐filtered effluent.…”
Section: Disinfection Methodsmentioning
confidence: 99%
“…Se ha demostrado el efecto de agua ozonizada sobre los virus que contienen lípidos en su estructura, los cuales han mostrado ser sensibles a este tratamiento, así como también sus cápsides 243 . El efecto observado fue la disrupción o pérdida estructural que resulta en pérdida de la infectividad.…”
Section: ¿Es Recomendable La Utilización De Aditamentos Y Mecanismos ...unclassified